PENDEKATAN DALAM PENYELESAIAN SENGKETA PERUSAHAAN ASURANSI - Syaiful Anam (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2021)
Abstrak Introduction: Insurance is an agreement whereby the insurer binds himself to the insured by accepting a premium to compensate him for the loss, damage or loss of expected profit that he may suffer as a result of an event (uncertain event). Methods: The method used in this research is a normative juridical approach, with analytical descriptive specifications, while the data collection techniques use primary data and secondary data. Results: Today, the Indonesian people have realized the important role of the insurance industry in providing security guarantee against the risks that will occur, so they gradually tie themselves to several insurance companies in Indonesia. However, like companies in general, the existence of an insurance company has also experienced several disputes, such as cases of insurance claims that were not disbursed and even rejected by the insurance company. Of course this case requires a resolution as regulated in law. Based on Financial Services Authority Circular Letter Number 2 / Seojk.07 / 2014, there are two alternative dispute resolution options between Financial Services Business Actors and consumers, namely litigation and non-litigation. Conclusion and suggestion: Insurance disputes often occur between insurance companies and consumers who have tied himselves to the company. The law provides for the resolution of insurance disputes by providing two alternative solutions. Namely through litigation and non-litigation. In terms of non-litigation, the Financial Services Authority has established an Alternative Institution for Financial Services Sector Dispute Resolution as regulated in POJK Number 61 / POJK.07 / 2020. Keywords: Despute, resolution, insurance